Lampbrush chromosome loop-specificity of transcript morphology in spermatocyte nuclei of Drosophila hydei - de Loos, Frans (1984)
The transcript morphology in the lampbrush chromosome loop pairs `threads' and `pseudonucleolus' of the Y chromosome in primary spermatocytes of Drosophila hydei has been investigated by the Miller spreading technique. Each loop pair carries giant transcripts with a secondary structure characteristic of the respective loop. The lengths of the transcribed regions are in the range 500–1500 kb or even larger. The results of our experiments are discussed in the context of loop ultrastructure, molecular structure and loop function. The high degree of secondary structure may be required to assemble specifically loop-specific proteins.